Functional connectivity in mild traumatic brain injury - Mayer, Andrew R. (Wiley Subscription Services, Inc., A Wiley Company, 2011)
Objectives: Research suggests that the majority of mild traumatic brain injury (mTBI) patients exhibit both cognitive and emotional dysfunction within the first weeks of injury, followed by symptom resolution 3–6 months postinjury. The neuronal correlates of said dysfunction are difficult to detect with standard clinical neuroimaging, complicating differential diagnosis and early identification of patients who may not recover. This study examined whether resting state functional magnetic resonance imaging (fMRI) provides objective markers of injury and predicts cognitive, emotional, and somatic complaints in mTBI patients semiacutely (<3 weeks postinjury) and in late recovery (3–5 month) phases. Methods: Twenty‐seven semiacute mTBI patients and 26 gender, age, and education‐matched controls were studied. Fifteen of 27 patients returned for a follow‐up visit 3–5 months postinjury. The main dependent variables were spontaneous fluctuations (temporal correlation) in the default‐mode (DMN) and fronto‐parietal task‐related networks as measured by fMRI. Results: Significant differences in self‐reported cognitive, emotional, and somatic complaints were observed (all P < 0.05), despite normal clinical (T1 and T2) imaging and neuropsychological testing results. Mild TBI patients demonstrated decreased functional connectivity within the DMN and hyper‐connectivity between the DMN and lateral prefrontal cortex. Measures of functional connectivity exhibited high levels of sensitivity and specificity for patient classification and predicted cognitive complaints in the semi‐acute injury stage. However, no changes in functional connectivity were observed across a 4‐month recovery period. Conclusions: Abnormal connectivity between the DMN and frontal cortex may provide objective biomarkers of mTBI and underlie cognitive impairment. Hum Brain Mapp, 2011. © 2011 Wiley‐Liss, Inc.